Occupations at high risk for malaria in Zanzibar: a case–control study, may–august 2023 - Geofrey Makenga; Sarah Gallalee; Humphrey Mkali; Mwinyi Issa Khamis; Abdulhamid Ramadhan; Mohamed Haji Ali; Wahida S. Hassan; Juma Hassan; Stella Makwaruzi; Saidi Mgata; Michael Gulaka; Nicodem James Govella; et al. (Malaria Journal)
Abstract Background In malaria elimination settings, cases tend to cluster geographically and occur among certain subpopulations. Clustering is often related to specific factors such as occupation or mobility, which increase an individual’s risk for malaria infection. Methods A case–control study was conducted to identify malaria high-risk populations (HRPs) in Zanzibar. Patients presenting with symptoms of malaria at selected facilities were recruited from historically high burden areas in two urban districts (Mjini and Magharibi B) and two rural districts (Kati and Micheweni). Between May and August 2023, the study recruited 197 cases and 557 controls frequency matched by age group and sex. Logistic regression was used to explore associations between risk factors and the epidemiological outcome of local malaria infection, classified as confirmed malaria cases with no travel outside Zanzibar in the prior 3 weeks. Results In urban districts, night watchmen/police (odds ratio [OR] 5.3, 95% confidence interval [CI]: 2.7–10.6, p < 0.001), construction workers (OR 3.0, 95% CI 1.8–5.0 p = 0.007), and farmers (OR 1.6, 95% CI 1.1–2.2, p = 0.01) were found to have higher odds of malaria infection compared to those not working in those professions. Other high-risk behaviours in urban districts included night-time activities (OR 2.8, 95% CI 1.8–4.3, p < 0.001), meals taken outside (OR 2.0, 95% CI 1.1–3.4, p = 0.01), and recent travel within Zanzibar (OR 3.3, 95% CI 1.5–7.1, p = 0.002). In rural districts, outdoor night-time activities (OR 3.8, 95% CI 1.5–9.9, p = 0.006) and taking meals outside (OR 2.7, 95% CI 1.1–6.6, p = 0.03) were risk factors for malaria; however, no higher risk occupational groups were identified. Overall, there was a trend towards net use being protective against malaria, but this association only reached statistical significance in rural districts (p = 0.015). Conclusion Tailored interventions targeting specific occupational groups could be an effective strategy to reduce malaria in urban areas in Zanzibar.